Split Hopkinson pressure bar tensile testing - Muhammad Hafiq Rosli (Nanyang Technological University, 2021)
The Split Hopkinson Pressure Bar (SHPB) is an experimental technique used to investigate the mechanical properties of a material at different loading conditions under high strain rates, ranging from 1,000s-1 to 10,000s-1 . There are three types of techniques, namely tension, compression, and torsion. This report focuses only on the tensile aspect of the SHPB. The SHPB tensile experiment requires the generation of longitudinal waves that propagates along the experimental setup. The strain gauges located on the input and output bar then measures these longitudinal waves. The data collected by the strain gauge is then channelled and displayed on the Yokogawa oscilloscope where the stress, strain and strain rate are then calculated and analysed. Unlike the past, the main objective of this current project is to repair and recalibrate the SHPB tensile machine. This is due to the machine not being able to operate at optimum performance. This project involves dismantling the machine to analyse the issue and make necessary repairs before assembling the machine again. The machine is then realigned and recalibrated to ensure that the machine can operate at optimum capabilities again. To verify the performance of the machine, a simple test with specimen is then conducted to obtain similar results as previous project. This report will also discuss the various challenges faced and solutions recommended for further improvements.